2015
DOI: 10.1111/bjd.13295
|View full text |Cite
|
Sign up to set email alerts
|

Nano-TiO2modulates the dermal sensitization potency of dinitrochlorobenzene after topical exposure

Abstract: We have demonstrated that topical exposure to TiO2 ENPs increases chemical-induced dermal sensitization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
29
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 29 publications
1
29
0
Order By: Relevance
“…Studies in mice have addressed the pro-allergic potential of Au, TiO 2 , and SiO 2 NPs in contact hypersensitivity. Such reactions are characterized by a T cell-mediated delayed-type adverse response without the presence of allergen-specific IgE or airway hyperresponsiveness with eosinophil infiltration, mucous cell metaplasia, and elevated type 2 cytokine secretion (106108). Graphene nanosheets and multiwalled carbon nanotubes (MWCNTs) have been shown to induce a T H 2 immune response in mouse models when administered intravenously (109).…”
Section: Allergymentioning
confidence: 99%
“…Studies in mice have addressed the pro-allergic potential of Au, TiO 2 , and SiO 2 NPs in contact hypersensitivity. Such reactions are characterized by a T cell-mediated delayed-type adverse response without the presence of allergen-specific IgE or airway hyperresponsiveness with eosinophil infiltration, mucous cell metaplasia, and elevated type 2 cytokine secretion (106108). Graphene nanosheets and multiwalled carbon nanotubes (MWCNTs) have been shown to induce a T H 2 immune response in mouse models when administered intravenously (109).…”
Section: Allergymentioning
confidence: 99%
“…[16][17][18] It is obvious that nanostructures can penetrate human cells through inhalation, ingestion, dermal contact and injection. [19][20][21][22] They could be easily distributed into the blood circulation systems and from there to sensitive organs. 23,24 They also have shown side effects on blood cells.…”
Section: Introductionmentioning
confidence: 99%
“…These results were confirmed by more recent studies reported by the TGA . Indeed, two studies performed in mice showed no skin sensitization after dermal application of nano‐TiO 2 on the ears for 3 days . However, nano‐TiO 2 was shown to increase dermal sensitization induced by 2,4‐dinitrochlorobenzene …”
Section: Toxicitymentioning
confidence: 99%
“…24 Indeed, two studies performed in mice showed no skin sensitization after dermal application of nano-TiO 2 on the ears for 3 days. 1,54 However, nano-TiO 2 was shown to increase dermal sensitization induced by 2,4-dinitrochlorobenzene. 54 Concerning skin irritation, the studies analysed by the SCCS provided only limited relevant information.…”
Section: Dermal Toxicitymentioning
confidence: 99%
See 1 more Smart Citation